2022
DOI: 10.1088/1755-1315/1022/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

A review of steel fiber’s potential use in Hot Mix Asphalt

Abstract: The purpose of this paper is to overview the potential use of steel fibre in hot mix asphalt, explore the evolution of steel fibre reinforced asphalt concrete (SFRAC), highlights current trends in research and industry and recommend future areas of research. The study focus on the steel fibre industry and steel fibre generated from waste tyres applied in asphalt pavement. This review focuses on the use and performance of these fibres in altering the performance of asphalt pavements in terms of fibre concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…Among the polymer fiber that is regularly used in asphalt mixtures, for this reason, are steel, glass, natural, and synthetic fiber. This result is in line with a recent study that found the presence of fibers changes the mixture's viscoelasticity, increases its dynamic modulus, improves its sensitivity to humidity, improves flow coherence, and prevents rutting [6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the polymer fiber that is regularly used in asphalt mixtures, for this reason, are steel, glass, natural, and synthetic fiber. This result is in line with a recent study that found the presence of fibers changes the mixture's viscoelasticity, increases its dynamic modulus, improves its sensitivity to humidity, improves flow coherence, and prevents rutting [6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 90%
“…Steel fiber is one of the new potential additives to asphalt mixes that demonstrate a high durability pavement, increasing the base's fatigue life and enhancing resistance to reflective asphalt cracking [8]. The excellent performance of steel fiber indicates that the material may provide a combination of high functionality and good mechanical properties [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The study into the incorporation of steel fibre in hot mix asphalt also draws the attention of researchers, who believe that it is advantageous for enhancing the strength of asphalt hot mix [38]. A research on steel fibre-reinforced asphalt concrete was conducted to evaluate several factors of steel fibres, such as aspect ratio, section type, and roughness by evaluating the cracking resistance using an indirect tension test at low temperatures.…”
Section: Pavement and Road Constructionmentioning
confidence: 99%
“…It is important to note that the steel fibres collected from discarded tyres come in different shapes and lengths, and may also include rubber contamination. These attributes influence the efficiency of this substance when integrated into hot mix asphalt [38].…”
Section: Pavement and Road Constructionmentioning
confidence: 99%